Methyl violet dye removal using coal fly ash (CFA) as a dual sites adsorbent. Issue 5 (October 2019) - Astuti, Widi; Chafidz, Achmad; Wahyuni, Endang Tri; Prasetya, Agus; Bendiyasa, I. Made; Abasaeed, Ahmed E.
Abstract: It has become a trend to use cheap adsorbents like coal fly ash (CFA) for removal of dyes. CFA is a solid waste produced from coal-based power plant. CFA is mainly composed of minerals containing some oxides such as Al2 O3 and SiO2 having active sites and mesoporous unburned carbon. The existence of active sites in the CFA's minerals and carbon pores was considered to have roles in the adsorption process with different adsorption mechanisms, namely chemisorption for the minerals and physisorption for the unburned carbon. This allows the CFA to become a dual sites adsorbent. As the result, isothermal models such as Langmuir and Freundlich may not be appropriate. The objectives of this study are to develop appropriate dual sites isotherm models for methyl violet dye adsorption onto the CFA, and to compare the models with single site models including Langmuir and Freundlich. The CFAs having [Si + Al]/C ratio of 0.5, 2.0 and 90, namely CFA-1, CFA-2, and CFA-3, respectively were used in this study. X-Ray Fluorescence (XRF) analysis results showed that the major components of the original CFA are SiO2 (36.47%) and Al2 O3 (19.27%), while the unburned carbon content is 19.11%. Additionally, the adsorption test results showed that CFA with high unburned carbon contents (i.e. CFA-1 and CFA-2) were well fitted with the dual sites isotherm model, i.e. Freundlich–Langmuir isotherm model. Whereas, CFA with low unburned carbon contents (i.e. CFA-3) was well fitted with the single site isotherm model, i.e. Langmuir isotherm model.